WEB-BASED SPP PAYMENT INFORMATION SYSTEM WITH MIDTRANS PAYMENT GATEWAY - Aditya, Mulyadi; Sulistyowati, Daning Nur (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
ABSTRACT- The tuition payment system at Taufiq Islamic Middle School is still manually using ledger media in transaction activities and data recap. The system still needs to be revised and is prone to errors in calculating incoming payments and reporting payment data. This research was conducted to facilitate the school in the payment management process so that the recording error rate no longer occurs. The system development method used in this study is the Waterfall model and uses the Midtrans payment gateway in the online payment process. The results of this study are in the form of a tuition payment website that can facilitate all parties, both the school and students. This system makes the payment and recording process better and more efficient. Keywords: information system, waterfall, payment gateway, Midtrans.